A Case of an Obstructed Delivery by a Large, Lower Uterine Segment Fibroid Interlocked with a Fetal Mentum - Miller, Sarah E.; Miller, Hayley E.; Waldrop, Anne R.; Karakash, Scarlett D.; Shaw, Kate A. (American Journal of Perinatology Reports, 2024)
Uterine leiomyomata are associated with many pregnancy complications and will likely become increasingly common as the average age of childbearing increases. We describe a case of an obstructed delivery by a large fibroid. A 37-year-old G2P1001 with a 10-cm anterior, lower uterine segment fibroid presented for labor induction. Labor was complicated by arrest of descent due to suspected obstruction of the fetal body by the fibroid after descent of the fetal head, and delivery during cesarean section was complicated by apparent interlocking of the fetal mentum with the fibroid. Large, anterior lower uterine segment fibroids have the potential to obstruct delivery of the fetal head or of the fetal body, and these patients should be counseled regarding the potential for complications via both vaginal and cesarean deliveries.
Keywords: cesarean section; leiomyomas of the uterus; obstructed delivery; labor; management